Association between personal characteristics and health beliefs with pre-mammography anxiety in women referred to mammography centers - Farkhonde Hayati; Simin Jahani; Parvaneh Mousavi; Mohammad Hossein Haghighizade (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2017)
Introduction: Breast cancer is the most common malignancy in women which is potentially fatal in the case of no early diagnosed and no effective treatment. The role of beliefs in screening behavior is very useful to control disease. Therefore, this study was performed with aim to determine the relationship between personal characteristics and health beliefs with anxiety before mammographyin women referred to mammography centers. Methods: This descriptive study was performed in 2010 on 120 women referred to two mammography centers in Ahvaz. The subjects were selected by convenience sampling and they asked to three questionnaires of demographic and clinical characteristics, health beliefs and situational anxiety. Data was analyzed by SPSS software (version 18), and descriptive statistics (mean, standard deviation, absolute and relative frequency) and inferential statistics of Pearson correlation and linear regression. P<0.05 was considered significant. Results: In this study, 64 cases (53.3%) had mild anxiety. Significant relationship was found between age and anxiety (p=0.001) and also between monthly income and anxiety (p=0.031). There was significant relationship between the numbers of mammography and anxiety (p=0.000). No significant relationship was observed between the total scores of health beliefs about barriers to perform mammography and perceived susceptibility toward breast cancer and anxiety (p=0.55). Conclusion: Designing and implementation of extensive training programs at the community level can have a significant impact in correcting and promoting of women's attitudes and knowledgeTop of Form ‏ about health behaviors of prevention and screening for breast cancer.